MAGICAL REALISM IN THE CONTEXT OF POSTMODERN AESTHETICS: HERMANN KASACK’S “THE CITY BEYOND THE RIVER” AND MAX KIDRUK’S “DON’T LOOK BACK AND STAY QUIET” INTER- TEXTUAL CONNECTIONS - Tetiana V. Bykova; Nina D. Osmak (Alfred Nobel University Journal of Philology)
The article is devoted to revealing the main characteristics of Magical Realism as a central feature of postmodern text in the novels by Hermann Kasack “The City Beyond the River” and Max Kidruk “Don’t Look Back and Stay Quiet”. The intertextual connection between both texts is noted, encompassing mutual references and links to ancient Greek mythology. The main symbolism of the works is analysed, and the ideological content of the text is revealed. The aim of the article is to identify the main postmodern features of Magical Realism in the novels by H. Kasack “The City Beyond the River” and M. Kidruk “Don’t Look Back and Stay Quiet”. The primary objectives are to trace the main textual connections between the works of German and Ukrainian authors H. Kasack and M. Kidruk at the intertextual level and at the same time to reveal individual authorial expressions of Magical Realism as one of the main characteristics of the works of postmodern literature. To achieve the stated aim and solve the set tasks, historical-literary, hermeneutic, mythopoetic methods, as well as the method of intertextual analysis, were used. As a result of a study, a consonance between Magical Realism and Postmodernism was identified, which is present at the ideological level: the aesthetics of magical realism and postmodern aesthetics are based on an epistemological crisis caused by a doubt about the legitimacy of “classical” knowledge and the process of cognition. While Postmodernism expresses doubt about the reliability of classical knowledge, magical realism confirms the legitimacy of alternative – non-empirical cognitive experience alongside the classical experience, vividly reflecting this in the strong connection between two realities (empirical and magical), which interact and coexist on equal terms within the work. At the same time, it can be noted that during the postmodern era, the aesthetics of magical realism undergoes transformations. In its traditional principles, which are defined by the use of irresistible element of magic, the presence of realism in magical realism, the violation of conventional notions of time, space and identity, and the attempt to reconcile two contradictory understandings of events (according to V. Faris), the existential idea is realized. Within this framework, philosophical questions about human existence and the experience of one’s way of being, the issues of loneliness and death, the meaning of life, personal freedom, knowledge, and self-awareness are explored. The works of H. Kasack and M. Kidruk serve as vivid examples of German and Ukrainian Magical Realism. The magical and realistic dimension of existential issues is emphasized by intertextuality, in which the text of the German writer’s novel becomes a palimpsest of Ukrainian postmodern literature: through H. Kasack’s novel “The City Beyond the River” in M. Kidruk’s novel “Don’t Look Back and Stay Quiet”, an allusive connection to ancient texts is established and is reinterpreted on a national basis – through folklore motifs and images. The principle of intertextuality is key to the artistic construction of both works and is manifested across several levels in both novels: 1) existential themes and issues, particularly in exploration of death, understanding the problems of experiencing one’s way of being and the problems of cognition / self-knowledge; 2) at the level of the plot, where the key to both novels is the transformation of the myth about Orpheus and Eurydice with a reinterpreting of the motif of breaking the taboo; 3) at the motif level, through the meaning-making and plot-shaping functions of the motifs of numbers, journeys, and mirrors; 4) at the chronotopic level, through the symbolic representation of time and space in magical realism; 5) at character level, through the creation of a new type of hero who possesses sacred knowledge; 6) finally, at the level of ideological transformation and the external return to oneself, through the exploration of the problem of life and death, and the idea of inability of scientific knowledge for the complete understanding of both the human being and the world. Through symbolic markers, the works depict the author’s contemporary reality, and the events that take place do not obey everyday life. The postmodern means of magical realism used by the writers H. Kasack and M. Kidruk form the literary space of the text, interact with other literary movements and styles, such as surrealism, existentialism, etc.